Elements of workers turnover intention in fast food restaurant at Chukai, Kemaman, Terengganu / Nur Fathiah Nazmin and Nur Sakinah Ramlan - Nazmin, Nur Fathiah; Ramlan, Nur Sakinah (2019)
This research proposal was about the element of worker turnover intention in fast food restaurant at Chukai, Kemaman, Terengganu. The purpose of this study was focus on factor effected the worker turnover. In Malaysia fast food industry, this problem was handled for many years but it is still become a major problem. Many study has examined the factor of employee turnover in fast food industry but there is a gap in between turnover of employee and turnover of worker. There are several differences between workers and employee which are, workers are people who was working in the organisation without long contract or in other words, it can call as part-timers workers compared to employee who was basically work as permanent. Therefore, this study examines whether the salary and wages affected the turnover intention. Hence, the researcher also focusing to examine whether there is relationship between employers and workers and the management style affect the turnover. The respondent that might be involved is the workers at the fast food restaurant around Chukai, Kemaman and also the managers and supervisors.